The effect of pictorial story media on critical thinking of grade 4 SDN 1 Pendem - Yulina Ismiyanti; Novia Dwi Permatasari (Jurnal Ilmiah Pendidikan Dasar, 2021)
The background of this research is that teachers have not used innovative learning media in social studies learning which still tends to be conventional. Critical thinking ability is less motivated due to not using learning media as a facility. The purpose of this study was to analyze the influence of pictorial story media on critical thinking skills. This type of research is an experiment with a pre-test post-test control design. The total population was 40 class 4 students of SDN 1 Pendem. The sample was taken randomly with a significant amount of 5% to obtain 36 students. The data collection used was a critical ability test as the main data, interviews, and documentation as supporting data. The pre-test test instrument includes validity, reliability, discriminating power, and level of difficulty. The data were tested with the normality test, because the data were obtained with a normal distribution, the t-test was tested. The test results obtained t count => - t table or 9.668 => -2.030. It can be concluded has a significant effect on the use of pictorial media stories on critical thinking skills.